2016
DOI: 10.2174/1874123101610010059
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification in Liquid-Liquid Equilibrium Modeling of Food-Related Thermodynamic Systems Using Flower Pollination Algorithms

Abstract: In this paper, the liquid–liquid equilibrium of twenty two ternary and quaternary systems relevant for food industry was modeled using the NRTL and UNIQUAC equations and the Flower Pollination Algorithm (FPA). FPA is an emerging nature-inspired stochastic global optimization method and it has been used for LLE parameter identification of local composition models in multicomponent mixtures. FPA and its modified version (MFPA) were assessed for solving LLE parameter estimation problems in several systems relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…EHA-C and EHA, respectively). 31 These equations describe a linear relationship among the binary interaction parameters of the limited composition models for multicomponent mixtures and may be defined as follows for ternary systems…”
Section: Data Correlationsupporting
confidence: 88%
See 1 more Smart Citation
“…EHA-C and EHA, respectively). 31 These equations describe a linear relationship among the binary interaction parameters of the limited composition models for multicomponent mixtures and may be defined as follows for ternary systems…”
Section: Data Correlationsupporting
confidence: 88%
“…Additionally, the performance of the EHA has been checked in the presence and absence of the application of closure equations (i.e. EHA-C and EHA, respectively) . These equations describe a linear relationship among the binary interaction parameters of the limited composition models for multicomponent mixtures and may be defined as follows for ternary systems …”
Section: Resultsmentioning
confidence: 99%
“…The UNIQUAC model is where θ i and Ø i represent the surface and volume fractions of compound i , respectively. q and r are surface area and relative volume, a ij is an interaction parameter which is regarded as an adjustable parameter for UNIQUAC model.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are some studies conducted by researchers about the applications of FPA in chemical engineering. Merzougui et al [125] applied FPA for phase equilibrium calculations of a Liquid-Liquid Equilibrium system in which the algorithm had been utilized for…”
Section: B Chemical Engineeringmentioning
confidence: 99%
“…The experimental outcomes showed that the suggested algorithm comparatively performs better to obtain the global minimum of the potential energy function [124]. [125], [126].…”
Section: Hfpgamentioning
confidence: 99%